Preparation method and application of adsorption-photocatalysis bifunctional MILs material
By preparing the adsorption-photocatalytic dual-function MILs material Ti/Fe-MIL-101 with both oxygen vacancy and high iron oxidation activity, the problems of large mass transfer resistance and low degradation efficiency of trace organic pollutants in water are solved, and high efficiency is achieved Adsorption and photocatalytic removal effects and demonstrate good cycle regeneration performance.
Patent Information
- Application Number
- CN202411384962.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-07
AI Technical Summary
The prior art has problems of large mass transfer resistance and low degradation efficiency when treating trace organic pollutants in water. Single adsorption method or photocatalytic method has its drawbacks, and it is difficult to improve adsorption and photocatalytic performance at the same time.
Using a preparation method of Ti/Fe-MIL-101, an adsorption-photocatalytic dual-function MILs material with both oxygen vacancy and high valence iron oxidation activity, the metal Ti is introduced through a one-step synthesis method to broaden the visible light absorption range, enhance the pore size of the material and Surface oxygen vacancy improves adsorption and photocatalytic properties.
It has achieved efficient removal of trace organic pollutants in water, significantly improved adsorption capacity and photocatalytic degradation rate, exhibited higher efficiency compared with undoped and other metal-doped materials, and had good cycling and regeneration capabilities.
Smart Images

Figure CN119259011A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of water pollution treatment materials, and in particular to a preparation method and application of an adsorption-photocatalysis dual-functional MILs material. Technical Background
[0002] The concentration of emerging organic pollutants (EOCs) in water ranges from about ng / L to ug / L, but they are persistent, ecotoxic, and difficult to biodegrade. Conventional sewage treatment plant treatment technologies, such as coagulation, sedimentation, and biofilm treatment, have very limited effects on EOCs removal. Adsorption and photocatalysis have the advantages of high removal rate, simple operation, and green environmental protection, and have become important technologies for treating trace EOCs in water. At present, the single adsorption method has the disadvantages of easy saturation of the adsorbent, difficulty in regeneration, and the ultimate inability to degrade pollutants. Although the single photocatalysis method can use sunlight to produce reactive species (ROS), including ·OH - , O2 - and 1 O2, etc., directly degrade pollutants on the catalyst surface. However, the single photocatalytic method is easily affected by the mass transfer resistance of pollutants in water under extremely low pollutant concentration conditions, resulting in a reduced degradation rate. Therefore, the adsorption synergistic photocatalytic method can first reduce the mass transfer resistance of trace EOCs in water through adsorption, pre-enrich the pollutants on the catalyst surface, and then degrade them in situ photocatalytically. It has become one of the methods for efficiently removing EOCs in water.
[0003] However, since the adsorption sites often compete with the photocatalytic sites, the adsorbent cannot have efficient photocatalytic performance, and common photocatalysts are also difficult to quickly adsorb trace organic micropollutants. MIL-101(Fe), as a typical metal organic framework material of the MILs series, has a large specific surface area and adjustable pore size, and thus has a strong adsorption capacity. At the same time, the presence of Fe-O clusters makes it responsive to visible light, and Fe 3+ / Fe 2+ The redox reaction between them provides a direction for electron transfer, can effectively inhibit carrier recombination, and has potential for photocatalytic applications. The wide band gap and limited visible light response of MIL-101(Fe) are the main reasons that limit its photocatalytic performance. Metal doping, functional group modification and heterojunction construction have been used to improve these drawbacks. Among them, metal doping has attracted much attention due to its simple operation and significant effect. However, the one-step improvement of the adsorption and photocatalytic effect of metal-organic framework materials on trace organic pollutants in water by metal doping needs to be further strengthened. Summary of the invention
[0004] In view of this, the present invention provides a preparation method and application of a MILs material with dual functional sites of adsorption and photocatalysis to solve the problems of large mass transfer resistance and low degradation efficiency of trace organic pollutants. The synthesis process is simple and easy to operate. The modified metal organic framework material of the present invention has both oxygen vacancies and high-valent iron oxidation activity, and can efficiently remove trace organic pollutants in water.
[0005] The present invention provides a one-step synthesis method of an adsorption-photocatalytic dual-functional MILs material having both oxygen vacancy defects and photoexcited high-valent iron oxidation activity, comprising the following steps:
[0006] (A) An iron source and an organic ligand are added to an organic solvent, subjected to ultrasonic treatment and stirred to obtain a solution A.
[0007] (B) Adding a metal source to solution A, ultrasonically treating the solution and stirring the solution to obtain a mixed solution B.
[0008] (C) The mixed solution B is subjected to a solvothermal reaction under high pressure conditions, and after natural cooling, it is separated, washed, and dried to obtain an adsorption-photocatalytic dual-functional MILs material having both oxygen vacancies and high-valent iron oxidation activity, which is named "M / Fe-MIL-101" in the present invention.
[0009] Preferably, the iron source is ferric chloride hexahydrate; the metal source is titanocene dichloride, isopropyl titanate, titanium tetrachloride, cerium acetate, cerium nitrate, cerium chloride, cupric acetate, cupric chloride, aluminum nitrate or aluminum chloride, preferably titanocene dichloride; the molar ratio of the added metal source to the iron source is 1:10-3:10; preferably, the molar ratio of the iron source to the metal source is 10:1.
[0010] Preferably, the organic ligand is terephthalic acid.
[0011] Preferably, the organic solvent is N,N-dimethylformamide.
[0012] Preferably, the ultrasonic treatment time in step (A) and step (B) is 30 min.
[0013] Preferably, the stirring in step (A) and step (B) is magnetic stirring, and the stirring time is 30 minutes.
[0014] Preferably, the solvothermal reaction in step (C) is carried out in a high pressure reactor equipped with a polytetrafluoroethylene liner.
[0015] Preferably, the solvent thermal reaction temperature is 110° C. and the reaction time is 20 h.
[0016] Preferably, the solid is separated by centrifugation, and the obtained product is washed three times with N,N-dimethylformamide and ethanol respectively.
[0017] Preferably, the product is dried under vacuum drying conditions at a temperature of 80° C. for 12 h.
[0018] In one aspect of the present invention, a metal organic framework material having both adsorption and photocatalytic functions is provided, namely Ti / Fe-MIL-101, and the material is prepared by the above method.
[0019] In another aspect of the present invention, the Ti / Fe-MIL-101 of the present invention contains a large number of oxygen vacancies and highly active high-valent metals, and can be used for adsorption and synergistic photocatalytic removal of trace organic pollutants in water; preferably, the organic pollutants are diclofenac sodium, naproxen, bisphenol A, ibuprofen, ciprofloxacin, tetracycline and chlortetracycline.
[0020] The present invention provides an adsorption-photocatalytic bifunctional metal organic framework material Ti / Fe-MIL-101 having both oxygen vacancy defects and photoexcited high-valent iron oxidation activity and a one-step synthesis method thereof. The introduction of metal Ti can effectively broaden the visible light absorption range of MIL-101 (Fe), thereby reducing the band gap energy and accelerating carrier separation. In addition, Ti participates in the self-assembly process of the bifunctional material as a new metal center, introduces ligand defects, enlarges the pore size of the material and forms oxygen vacancies on the surface of the material. The change in the pore structure and the appearance of surface oxygen vacancies enhance the adsorption performance of the bifunctional material, which can quickly pre-enrich the pollutants on the material surface and adsorb oxygen molecules, thereby activating the oxygen molecules to produce more active species (such as ·O2 - and 1 O2), effectively improving the photodegradation rate of organic pollutants.
[0021] Since the transition metal Ti has a higher oxidation state and electron density, it induces electron redistribution inside MIL-101(Fe), thereby improving the photocatalytic activity. The electronegativity of metal Ti is weaker than that of Fe, so the electrons tend to gather toward the Fe center, which leads to an increase in the electron state density at the Fe site, causing electrons to transfer between Fe and Ti, forming a built-in electric field inside Ti / Fe-MIL-101, and providing a new channel for photogenerated electron transfer. In MIL-101(Fe), electron transfer mainly originates from Fe 3+ / Fe 2+ The redox reaction between Ti 4+ After its introduction, Fe 3+ and Fe 2+ Prefer to donate electrons, thus producing Fe 4+ Fe(Ⅳ) can not only undergo redox reactions with the intermediate product H2O2 produced in the photocatalytic process to produce more active free radicals, but can also directly obtain electrons from pollutants to achieve direct degradation of pollutants.
[0022] The adsorption-photocatalytic dual-functional material Ti / Fe-MIL-101 provided by the present invention can realize light-excited Fe(IV) oxidation activity and promote adsorption-synergistic photocatalytic removal of trace organic pollutants. In actual water samples, the active free radicals generated by photocatalysis are easily quenched and inactivated by the presence of high concentrations of salt and natural organic matter. Therefore, the addition of non-radical degradation pathways helps to enhance the application of Ti / Fe-MIL-101 in actual water.
[0023] The technical solution of the present invention has the following beneficial effects:
[0024] 1. The preparation method of the present invention is simple to operate, and the adsorption and photocatalytic properties of the MILs material can be simultaneously improved through one-step doping.
[0025] 2. The Ti / Fe-MIL-101 prepared by Ti doping in the present invention can achieve efficient removal of trace emerging organic pollutants in water, and has significantly improved adsorption and catalytic degradation efficiency compared with other types of metal doping. Figure 4 and Figure 6 The results of adsorption capacity and photocatalytic degradation rate show that the saturated adsorption capacity of diclofenac sodium by Ti / Fe-MIL-101 can reach 2.580 mmol / g, which is 1.30, 1.20, 1.17 and 1.37 times higher than that of undoped MIL-101(Fe), cerium-doped, copper-doped and aluminum-doped materials, respectively; the apparent degradation rate of diclofenac sodium is increased by 7.56, 2.43, 2.79 and 5.52 times higher than that of undoped MIL-101(Fe), cerium-doped, copper-doped and aluminum-doped materials, respectively. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1(a) is an SEM image of various dual-functional materials prepared in Examples 1-2 and Comparative Examples 1-3, wherein a is Example 1, b is Example 2, c is Comparative Example 1, d is Comparative Example 2, and e is Comparative Example 3.
[0027] FIG1( b ) is a SEM and EDS image of various dual-functional materials prepared in Examples 1-2 and Comparative Examples 1-3.
[0028] Figure 2 These are XRD diagrams of various dual-functional materials prepared in Examples 1-2 and Comparative Examples 1-3.
[0029] FIG3( a ) is an EPR oxygen vacancy test graph of various bifunctional materials prepared in Examples 1-2 and Comparative Examples 1-3.
[0030] FIG3( b ) is an XPS spectrum O1s narrow spectrum of the dual-functional material prepared in Example 1-2.
[0031] Figure 4The saturated adsorption capacities of various bifunctional materials prepared in Examples 1-4 and Comparative Examples 1-3 for diclofenac sodium (DCF), chlortetracycline (CTC) and ibuprofen (IBP).
[0032] Figure 5 The adsorption equilibrium time of diclofenac sodium, chlortetracycline and ibuprofen by various bifunctional materials prepared in Examples 1-4 and Comparative Examples 1-3.
[0033] Figure 6 The photocatalytic apparent degradation rates of diclofenac sodium and chlortetracycline by various bifunctional materials prepared in Examples 1-4 and Comparative Examples 1-3.
[0034] Figure 7 UV-vis DRS graphs of various dual-functional materials prepared in Examples 1-2 and Comparative Examples 1-3.
[0035] Figure 8 Mott-Schottky plots of various bifunctional materials prepared in Examples 1-2 and Comparative Examples 1-3.
[0036] Fig. 9 The band gap structures of various dual-functional materials prepared in Examples 1-2 and Comparative Examples 1-3 are shown.
[0037] Fig.10 These are EIS graphs of various dual-functional materials prepared in Examples 1-2 and Comparative Examples 1-3.
[0038] Fig.11 This is the XPS spectrum of Ti / Fe-MIL-101 prepared in Example 2.
[0039] Fig.12 The removal effect of Ti / Fe-MIL-101 prepared in Example 2 on different organic pollutants (naproxen, bisphenol A, ibuprofen, ciprofloxacin, diclofenac, tetracycline and chlortetracycline).
[0040] Fig.13 The cyclic regeneration of Ti / Fe-MIL-101 prepared in Example 2 to remove diclofenac sodium.
[0041] Fig.14 This is the removal effect of Ti / Fe-MIL-101 prepared in Example 2 on diclofenac sodium in actual water samples. DETAILED DESCRIPTION
[0042] In order to further describe the invention, the following detailed description is given, with reference to examples, of a dual-functional metal-organic framework material Ti / Fe-MIL-101 having both oxygen vacancy defects and photoexcited high-valent iron oxidation active adsorption-photocatalysis, as well as its synthesis and application provided by the present invention.
[0043] Example 1
[0044] 5 mmol of FeCl3·6H2O and 2.5 mmol of H2BDC (terephthalic acid) were added into 40 mL of N,N,-dimethylformamide solvent, respectively, and ultrasonically treated for 30 min and magnetically stirred for 30 min to obtain a uniform solution.
[0045] The above solution was transferred into a 100 mL polytetrafluoroethylene reactor and maintained at 110 °C for 20 h.
[0046] After naturally cooling to room temperature, the solid was separated by centrifugation, and the obtained product was washed three times with N,N-dimethylformamide and ethanol respectively, and dried under vacuum at 80° C. overnight. The obtained product was MIL-101(Fe).
[0047] Example 2
[0048] 5 mmol of FeCl3·6H2O and 2.5 mmol of H2BDC were added into 40 mL of N,N-dimethylformamide solvent, ultrasonically treated for 30 min, and magnetically stirred for 30 min to obtain solution A.
[0049] 0.5 mmol of Cp2TiCl2 was added to solution A, ultrasonically treated for 30 min, and magnetically stirred for 30 min to obtain a mixed solution B.
[0050] The mixed solution was transferred into a 100 mL polytetrafluoroethylene reactor and maintained at 110 °C for 20 h.
[0051] After naturally cooling to room temperature, the solid was separated by centrifugation, and the obtained product was washed three times with N,N-dimethylformamide and ethanol respectively, and dried under vacuum at 80°C overnight. The obtained product was named Ti / Fe-MIL-101.
[0052] Example 3
[0053] 5 mmol of FeCl3·6H2O and 2.5 mmol of H2BDC were added into 40 mL of N,N-dimethylformamide solvent, ultrasonically treated for 30 min, and magnetically stirred for 30 min to obtain solution A.
[0054] 0.5 mmol of TiCl4 was added to solution A, ultrasonically treated for 30 min, and magnetically stirred for 30 min to obtain a mixed solution B.
[0055] The mixed solution was transferred into a 100 mL polytetrafluoroethylene reactor and maintained at 110 °C for 20 h.
[0056] After naturally cooling to room temperature, the solid was separated by centrifugation, and the obtained product was washed three times with N,N-dimethylformamide and ethanol respectively, and dried under vacuum at 80°C overnight. The obtained product was named Ti / Fe-MIL-101-2.
[0057] Example 4
[0058] 5 mmol of FeCl3·6H2O and 2.5 mmol of H2BDC were added into 40 mL of N,N-dimethylformamide solvent, ultrasonically treated for 30 min, and magnetically stirred for 30 min to obtain solution A.
[0059] 1.5 mmol of Ti(OC3H7)4 was added to solution A, ultrasonically treated for 30 min, and magnetically stirred for 30 min to obtain a mixed solution B.
[0060] The mixed solution was transferred into a 100 mL polytetrafluoroethylene reactor and maintained at 110 °C for 20 h.
[0061] After naturally cooling to room temperature, the solid was separated by centrifugation, and the obtained product was washed three times with N,N-dimethylformamide and ethanol respectively, and dried under vacuum at 80°C overnight. The obtained product was named Ti / Fe-MIL-101-3.
[0062] Comparative Example 1
[0063] 5 mmol of FeCl3·6H2O and 2.5 mmol of H2BDC were added into 40 mL of N,N-dimethylformamide solvent, ultrasonically treated for 30 min, and magnetically stirred for 30 min to obtain solution A.
[0064] 0.5 mmol of Ce(Ac)3 was added to solution A, ultrasonically treated for 30 min, and magnetically stirred for 30 min to obtain a mixed solution B.
[0065] The mixed solution was transferred into a 100 mL polytetrafluoroethylene reactor and maintained at 110 °C for 20 h.
[0066] After naturally cooling to room temperature, the solid was separated by centrifugation, and the obtained product was washed three times with N,N-dimethylformamide and ethanol respectively, and dried under vacuum at 80°C overnight. The obtained product was named Ce / Fe-MIL-101.
[0067] Comparative Example 2
[0068] 5 mmol of FeCl3·6H2O and 2.5 mmol of H2BDC were added into 40 mL of N,N-dimethylformamide solvent, ultrasonically treated for 30 min, and magnetically stirred for 30 min to obtain solution A.
[0069] 1.0 mmol of Cu(Ac)2 was added to solution A, ultrasonically treated for 30 min, and magnetically stirred for 30 min to obtain a mixed solution B.
[0070] The mixed solution was transferred into a 100 mL polytetrafluoroethylene reactor and maintained at 110 °C for 20 h.
[0071] After naturally cooling to room temperature, the solid was separated by centrifugation, and the obtained product was washed three times with N,N-dimethylformamide and ethanol respectively, and dried under vacuum at 80°C overnight. The obtained product was named Cu / Fe-MIL-101.
[0072] Comparative Example 3
[0073] 5 mmol of FeCl3·6H2O and 2.5 mmol of H2BDC were added into 40 mL of N,N-dimethylformamide solvent, ultrasonically treated for 30 min, and magnetically stirred for 30 min to obtain solution A.
[0074] 1.5 mmol of AlCl3 was added to solution A, ultrasonically treated for 30 min, and magnetically stirred for 30 min to obtain a mixed solution B.
[0075] The mixed solution was transferred into a 100 mL polytetrafluoroethylene reactor and maintained at 110 °C for 20 h.
[0076] After naturally cooling to room temperature, the solid was separated by centrifugation, and the obtained product was washed three times with NN, dimethylformamide and ethanol respectively, and dried under vacuum at 80°C overnight. The obtained product was named Al / Fe-MIL-101.
[0077] According to the SEM images of the samples of Example 1-2 and Comparative Example 1-3 in Figure 1(a), it can be seen that the MIL-101(Fe) obtained in Example 1 is a regular octahedron with a smooth surface, the Ce / Fe-MIL-101 obtained in Comparative Example 1 is a spindle-shaped, the Cu / Fe-MIL-101 obtained in Comparative Example 2 is a regular icosahedron, and the Al / Fe-MIL-101 obtained in Comparative Example 3 and the Ti / Fe-MIL-101 obtained in Example 2 have relatively rough surfaces. The morphologies of MIL-101(Fe) doped with different metals all vary to a certain extent, indicating that metal doping affects the crystallization state of the crystal. Figure 1(b) is the EDS image of Example 1-2 and Comparative Example 1-3. It can be observed that the doped metals are evenly distributed in MIL-101(Fe), indicating that the new metals are successfully doped.
[0078] according to Figure 2The XRD spectrum shows that the main characteristic diffraction peaks of the MIL-101 (Fe) synthesized in Example 1 appear at 5.55°, 5.88°, 8.44°, 8.69°, 8.98°, 9.33°, 10.03°, 16.34° and 18.72°, which are basically consistent with the MIL-101 (Fe) standard card. The spectrum shows that most of the diffraction peaks after doping are the same as the original MIL-101 (Fe), indicating that metal doping has not changed the framework structure of MIL-101 (Fe). A few new diffraction peaks appeared in the doped samples, which are attributed to the changes in the exposed crystal planes and the crystallization state of the crystals. In addition, the crystal diffraction peaks of Examples 1-2 and Comparative Examples 1-3 are sharper, indicating that the crystals maintain a high degree of crystallinity.
[0079] According to the oxygen vacancy test diagram of Example 1-2 and Comparative Example 1-3 in FIG3 (a), the paramagnetic signal intensity of Ti / Fe-MIL-101 at g=2.0003 is the strongest, proving that the formation of oxygen vacancies is indeed related to metal Ti doping. At the same time, from the O1s narrow spectrum of the XPS spectrum of Example 1-2 in FIG3 (b), it can be seen that the proportion of the -COOH peak in Example 2 is reduced from 26.1% to 12.2% compared with that in Example 1, and it can be inferred that the formation of oxygen vacancies is related to the lack of ligands.
[0080] Depend on Figure 4 From the saturated adsorption capacities of diclofenac sodium, chlortetracycline and ibuprofen in Examples 1-4 and Comparative Examples 1-3, it can be seen that Example 2 maintains the highest adsorption capacity for all three organic pollutants. Figure 5 The adsorption equilibrium time of diclofenac sodium, chlortetracycline and ibuprofen in Examples 1-4 and Comparative Examples 1-3 shows that Example 2 has the shortest adsorption equilibrium time for diclofenac sodium and chlortetracycline, and the adsorption equilibrium time for ibuprofen is only higher than Comparative Example 3, which proves that Example 2 has a faster adsorption rate for the three pollutants. Combining the adsorption capacity and adsorption rate results, Example 2 has the best removal efficiency for the three pollutants.
[0081] See also Figure 6 According to the apparent degradation rates of diclofenac sodium, chlortetracycline and ibuprofen in Examples 1-4 and Comparative Examples 1-3, it can be seen that the photocatalytic degradation rates of the three pollutants in Examples 2-4 and Comparative Examples 1-3 are improved to varying degrees compared with Example 1. The apparent degradation rates of diclofenac sodium, chlortetracycline and ibuprofen in Example 2 are the fastest, which are 0.0287, 0.0579 and 0.0222 min, respectively. -1 .
[0082] See also Figure 7UV-vis DRS diagrams of various dual-functional materials prepared in Examples 1-2 and Comparative Examples 1-3. Compared with Example 1 and Comparative Examples 1-3, the absorption edge of Ti / Fe-MIL-101 prepared in Example 2 is significantly red-shifted, which indicates that Ti doping broadens the light absorption range of MIL-101 (Fe). The Tauc diagram shows that the band gaps of MIL-101 (Fe), Ti / Fe-MIL-101, Ce / Fe-MIL-101, Cu / Fe-MIL-101 and Al / Fe-MIL-101 are 2.81 eV, 2.39 eV, 2.75 eV, 2.76 eV and 2.95 eV, respectively, which confirms that Ti doping effectively reduces the band gap width of MIL-101 (Fe). In addition, see Figure 8 According to the Mott-Schottky plots of various bifunctional materials prepared in Examples 1-2 and Comparative Examples 1-3, it can be seen that several samples are typical n-type semiconductors, and their conduction band potentials are: -0.72eV, -0.55eV, 0.09eV, -0.30eV and -0.38eV respectively. Combining the conduction band potential with the band gap energy, the energy band position diagram of the material can be obtained, as shown in Fig. 9 shown.
[0083] See also Fig.10 It can be observed from the EIS graphs of various bifunctional materials prepared in Examples 1-2 and Comparative Examples 1-3 that the resistance value of Ti / Fe-MIL-101 prepared in Example 2 is lower than that in Example 1 and Comparative Examples 1-3, indicating that the migration rate of photogenerated electrons in Ti / Fe-MIL-101 is faster and the carrier recombination rate is the slowest.
[0084] See also Fig.11 , XPS of Ti / Fe-MIL-101 prepared in Example 2 shows that after illumination, the Ti2p binding energy shows a positive shift of about 0.3 eV, and the Fe2p binding energy shows a negative shift of about 0.2 eV. The Fe2p orbital has a characteristic peak of Fe(Ⅳ) at a binding energy of 716.0 eV, and the Ti2p has a characteristic peak of Ti(Ⅳ) at 457.94 eV and 463.16 eV respectively. 3+ 3 / 2 peak and Ti 3+ 1 / 2 peak. Therefore, it can be inferred that the photogenerated electrons are transferred between Ti and Fe. The introduction of Ti(Ⅳ) generates an electron transfer channel between Fe and Ti on Ti / Fe-MIL-101, forming a built-in electric field, thereby increasing the efficient separation of carriers.
[0085] See also Fig.12, the comparison of the removal effect of Ti / Fe-MIL-101 prepared in Example 2 on different organic pollutants shows that Ti / Fe-MIL-101 shows good removal effect on seven organic pollutants, namely naproxen, bisphenol A, ibuprofen, ciprofloxacin, diclofenac, tetracycline and chlortetracycline. Its removal rates for 10 mg / L ibuprofen, ciprofloxacin, diclofenac sodium, tetracycline and chlortetracycline are 97.0%, 91.7%, 96.6%, 99.1% and 99.7% respectively, and its removal rates for 10 mg / L naproxen and bisphenol A are slightly inferior to the first five pollutants, which are 73.4% and 79.6% respectively.
[0086] See also Fig.13 As shown in the cyclic regeneration diagram of Ti / Fe-MIL-101 prepared in Example 2 to remove diclofenac sodium, after three cycles, Ti / Fe-MIL-101 can maintain a removal rate of more than 90% for 10 mg / L diclofenac sodium; after six cycles, the removal rate is still above 80%. This proves that the dual-functional material disclosed in the present invention with both oxygen vacancy defects and photo-excited high-valent iron oxidation activity has good cyclic regeneration ability.
[0087] See also Fig.14 , the removal effect diagram of Ti / Fe-MIL-101 prepared in Example 2 on diclofenac sodium in actual water samples shows that in actual water samples, the adsorption performance of Ti / Fe-MIL-101 on 500ug / L diclofenac sodium has decreased, but the unsaturation of the adsorption sites allows its photocatalytic activity to remain at a high level within 3h. In laboratory water, tap water, simulated surface water, simulated groundwater and Chaohu water, the removal rate of Ti / Fe-MIL-101 on 500ug / L diclofenac sodium is maintained at more than 90%; in pond water, the removal rate is slightly reduced, but still reaches 85.41%. This shows that the Ti / Fe-MIL-101 prepared in Example 2 shows excellent performance in removing trace organic pollutants in actual water samples.
[0088] The above embodiments are only used to illustrate the technical solution of the present invention, but not to limit it. It should be pointed out that, for those skilled in the art, several improvements and modifications can be made to the present invention without departing from the principle of the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.
Claims
1. A method for preparing a MILs material with adsorption-photocatalysis dual functions, characterized in that: The steps include: (A) adding an iron source and an organic ligand into an organic solvent, ultrasonically treating and stirring to obtain a solution A; (B) adding a metal source to solution A, ultrasonically treating and stirring to obtain a mixed solution B; (C) subjecting the mixed solution B to a solvothermal reaction under high pressure, separating, washing and drying after natural cooling to obtain an adsorption-photocatalytic bifunctional MILs material having both oxygen vacancy defects and photoexcited high-valent iron oxidation activity, named M / Fe-MIL-101; Wherein, the iron source in step (A) is ferric chloride hexahydrate or ferric nitrate, the organic ligand is terephthalic acid, and the organic solvent is N,N-dimethylformamide; the metal source in step (B) is dichlorotitanocene, isopropyl titanate, titanium tetrachloride, cerium acetate, cerium nitrate, cerium chloride, copper acetate, copper chloride, aluminum nitrate or aluminum chloride; preferably, the metal source is dichlorotitanocene, isopropyl titanate or titanium tetrachloride; more preferably, the metal source is dichlorotitanocene.
2. The preparation method according to claim 1, characterized in that: The molar ratio of the added metal source to the iron source is 1:10-3:10; preferably, the molar ratio of the iron source to the titanium source is 10:
1.
3. The preparation method according to claim 1, characterized in that: The volume of N,N-dimethylformamide is 30-40 mL; the ultrasonic treatment time in step (A) and step (B) is 30-60 min; and the stirring time is 30-60 min.
4. The preparation method according to claim 1, characterized in that: The solvent thermal reaction in step (C) is carried out in a high-pressure reactor equipped with a polytetrafluoroethylene liner, the reaction temperature is 110-120° C., and the reaction time is 20-24 hours.
5. The preparation method according to claim 1, characterized in that: The separation process in step (C) is completed by using a high-speed centrifuge, the high-speed centrifugal speed is 6000-8000r / min, the centrifugal time is 8-15min, and the washing liquid is N,N-dimethylformamide and anhydrous ethanol.
6. The preparation method according to claim 1, characterized in that: The drying process is carried out in a vacuum drying oven at a temperature of 60-80°C for 12-16 hours. 7 . M / Fe-MIL-101 having both adsorption and photocatalytic functions prepared by the preparation method according to any one of claims 1 to 6 .
8. Use of the M / Fe-MIL-101 according to claim 7 in the removal of trace organic pollutants in water by adsorption-synergistic photocatalysis.
9. The use according to claim 8, characterized in that: The organic pollutants are diclofenac sodium, naproxen, bisphenol A, ibuprofen, ciprofloxacin, tetracycline and chlortetracycline.
Citation Information
Patent Citations
Adsorption-photocatalysis bifunctional material and preparation method thereof, and application of adsorption-photocatalysis bifunctional material in volatile organic gas treatment process
CN106861626A
Ce / MIL-101 (Fe) composite material, preparation thereof and application of Ce / MIL-101 (Fe) composite material in degradation of organic dye
CN117085740A
Preparation method and application of Cu-MIL-101 (Cr)-Fe material
CN117946412A
Copper-doped iron metal-organic framework, preparation method thereof, and application method for activation of persulfate to treat organic wastewater
US20180185828A1
Cited By
Preparation method of water purification filler with adsorption and photo-Fenton properties
CN119869619A